Дополнения к фауне веснянок сем. Nemouridae (Insecta, Plecoptera) Средней Азии - Жильцова, Л.А. (Вестник зоологии, 1978)
At present 13 species of the Nemouridae family are known for Middle Asia. They belong to three subgenera: Nemoura s. str. (5 species), Amphinemura (6 species) and Protonemura (2 species). Areas of distribution of most species (except for М. cinerea, A. mirabilis and P. vaillanti) are limited by the mountains of Middle Asia, two species of the Nemoura subgenus and 3 species of the Amphinemura subgenus being known only in narrow-limited regions. The A. crenata species is restored as an independent species though related to A. mirabilis, but having distinct differences. The A. mirabilis species widely distributed and with a mountain-Asian area of distribution forms a peculiar subspecies А. mirabilis turkestanica subsp. п. in Middle Asia.